THE COMMUNITIES’ ROLE IN CARDIAC ARREST CARE WITH CARDIOPULMANORY RESUSCITATION IN OUT OF HOSPITAL - A'an Dwi Sentana (Jurnal Kesehatan Prima, 2017)
Cardiac arrest normally occurs out of hospital in which can threaten a person’s life. In some countries, the prevalence of out of hospital cardiac arrests has increased. American Heart Association (AHA) in 2013 published the statistic of hearth and stroke disease, it said that out-of- hospital cardiac arrest (OHCA) case in the United States reached 359,400 people. From those populations, 40.1% received a cardiopulmonary resuscitation (CPR) performed by people around the victim and it was found that victim’s survival by 9.5%. This indicates that the people surround the victim have crucial role in increasing the survival of cardiac arrest patient. A number of people who are able to give CPR assistance when meet the cardiac arrest patients unexpectedly are still relatively low and varies with the lowest percentage 1% to the highest of 44%. The experience of emergency encourages people to be aware on any assistance to be conducted before advanced medical helps. By knowing the various emergency cases, it is expected that the community can perform appropriate assistance againts the case.